Answer:
I can't see the questions properly
Step-by-step explanation:
It would be 4. Multiply each side by -1/5.
It would cancel out the -1/5 leaving -15 = x.
All the numbers in the first equation have a common factor of 2. Removing that gives
.. x +4y = 6
making it easy to solve for x
.. x = 6 -4y
My choice would be to solve for x using the first equation.
_____
On second thought, it might actually be easier to solve either equation for 8y. That term then directly substitutes into the other equation (equivalent to adding the two equations).
.. 8y = 3x -11 . . . . . from the second equation
.. 2x +(3x -11) = 12 . . . substituting into the first equation
.. 5x = 23 . . . . . . . . . . collect terms, add 11 (what you would get by adding the equations in the first place)
.. x = 4.6
.. y = (3*4.6 -11)/8 = 0.35
Answer:
the quadratic formula is ax^2 + bx + c", if the first one is expanded out I will be 6x^2+8x+27 so that's the answer
When I do what the problem statement says, I get 47° for the left angle and 58° for the right one. They are not congruent.